Development of 3D-printed vaginal devices containing metronidazole for alternative bacterial vaginosis treatment - Utomo, Emilia; Domínguez-Robles, Juan; Anjani, Qonita Kurnia; Picco, Camila J.; Korelidou, Anna; Magee, Erin; Donnelly, Ryan F.; Larrañeta, Eneko (International journal of pharmaceutics: X, 2023)
Bacterial vaginosis (BV) is an abnormal condition caused by the change of microbiota in the vagina. One of the most common bacteria found in the case of BV is Gardnerella vaginalis, which is categorised as anaerobic facultative bacteria. Currently, the available treatment for BV is the use of antibiotics, such as metronidazole (MTZ), in topical and oral dosage forms. The limitation of the currently available treatment is that multiple administration is required and thus, the patient needs to apply the drug frequently to maintain the drug efficacy. To address these limitations, this research proposed prolonged delivery of MTZ in the form of intravaginal devices made from biodegradable and biocompatible polymers. Semi-solid extrusion (SSE) 3D printing was used to prepare the intravaginal devices. The ratio of high and low molecular weight poly(caprolactone) (PCL) was varied to evaluate the effect of polymer composition on the drug release. The versatility of SSE 3D printer was used to print the intravaginal devices into two different shapes (meshes and discs) and containing two different polymer layers made from PCL and a copolymer of methyl vinyl ether and maleic anhydride (Gantrez™-AN119), which provided mucoadhesive properties. Indeed, this layer made from Gantrez™-AN119 increased ca. 5 times the mucoadhesive properties of the final 3D-printed devices (from 0.52 to 2.57 N). Furthermore, MTZ was homogenously dispersed within the polymer matrix as evidenced by scanning electron microscopy analysis. Additionally, in vitro drug release, and antibacterial activity of the MTZ-loaded intravaginal devices were evaluated. Disc formulations were able to sustain the release of MTZ for 72 h for formulations containing 70/30 and 60/40 ratio of high molecular weight/low molecular weight PCL. On the other hand, the discs containing a 50/50 ratio of high molecular weight/low molecular weight PCL showed up to 9 days of release. However, no significant differences in the MTZ release from the MTZ-loaded meshes (60/40 and 50/50 ratio of high molecular weight/low molecular weight PCL) were found after 24 h. The results showed that the different ratios of high and low molecular weight PCL did not significantly affect the MTZ release. However, the shape of the devices did influence the release of MTZ, showing that larger surface area of the meshes provided a faster MTZ release. Moreover, MTZ loaded 3D-printed discs (5% w/w) were capable of inhibiting the growth of Gardnerella vaginalis. These materials showed clear antimicrobial properties, exhibiting a zone of inhibition of 19.0 ± 1.3 mm. Based on these findings, the manufactured represent a valuable alternative approach to the current available treatment, as they were able to provide sustained release of MTZ, reducing the frequency of administration and thus improving patient compliance. [Display omitted]